(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we prove the existence of nonnegative solutions to the initial boundary value problems for the pseudo-parabolic type equation with weakly nonlinear sources. Further, we discuss the asymptotic behavior of the solutions as the viscous coefficient k tends to zero.